TINJAUAN HUKUM PENDAFTARAN HAK TANGGUNGAN BERDASARKAN UU NO. 4 TAHUN 1996 DI KABUPATEN SRAGEN - PAIMAN, PAIMAN (Dinamika Hukum, 2015)
The purpose of this research is to review and to analyze the implementation of mortgage rights in order to get legal certainty in the district of Sragen and the role of PPAT in the realization of mortgage rights registration process in the district of Sragen. The background is that in the Mortgage Rights Law (UUHT) above the conception of land and its connection with objects upon the concerning land, that the land is separated from all objects attached upon it or the ownership of land is apart from objects upon it, so that the owner of land rights and the owner of building rights if performing process of bank assurance, registration of mortgage rights should be conducted. It is problematic in society. Keyword : Mortgage Rights Registration